Oral mucosa lesions and oral symptoms in inflammatory bowel disease patients - Laranjeira, Nuno (2015)
"Background - Inflammatory Bowel Disease is known for its extra intestinal manifestations, the oral cavity is no exception. Objectives - The aim of this study was to evaluate the association between Inflammatory Bowel Disease and oral mucosa lesions and symptoms, and complementary to evaluate their possible relation with oral hygiene, smoking habits, drug therapy, duration and activity of the disease. Methods - Patients were selected from the Gastroenterology Clinic of a Portuguese tertiary referral hospital. This sample consisted of 113 patients previously diagnosed with ulcerative colitis or Crohn’s disease along with a control group of 58 healthy individuals that were accompanying the study group patients to their appointments. Clinical interviews and clinical examinations were performed for data collection. Results - The patients in the study group were more affected by oral symptoms (P=0.011), and showed a trend towards a higher incidence of oral mucosal lesions, even though statistical significance was not reached (8.8% versus 3.4% in the control group; P=0.159). Patients in active phase were the most affected. No differences were detected between Crohn’s disease and ulcerative colitis, or concerning smoking habits. The corticosteroid and immunosuppressant therapy seemed to increase the incidence of oral symptoms (P=0.052). The oral mucosa lesions increased and the oral symptoms decreased over the course of the disease, however without statistical significance. Conclusion - Oral mucosa’s lesions and oral symptoms were positively associated with Inflammatory Bowel Disease, mainly during disease activity periods and conceivably, associated with corticosteroid and immunosuppressant therapy."